A method for coating transition metal oxide electrode material with metal-organic framework compound
By constructing an amorphous organic cladding layer on the surface of the positive electrode material of the sodium ion battery, the problems of instability of the material at high voltage and poor air stability are solved, the high-pressure stability and specific capacity of the material are significantly improved, and excellent cycling stability is achieved.
Patent Information
- Application Number
- CN202411347346.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2044-09-26
AI Technical Summary
The existing sodium ion battery positive electrode materials are unstable at high voltages and have poor air stability, which limits the energy density and practical application of the battery.
A layer of amorphous organic cladding layer was constructed on the layered oxide surface of O3-type sodium ion battery by low-pressure vapor deposition method, with a thickness of 3-5 nm. Imidazole organic matter as ligand, and the reaction temperature and time were controlled between 80-150°C and 4-12 hours.
The high-pressure stability and air stability of the positive electrode material are improved, and the specific capacity and cyclic stability are achieved. After coating, the specific capacity of 130mAh·g-1 can be exerted at a current density of 200mA·g-1, and the capacity retention rate exceeds 86% after 200 weeks of cycle.
Smart Images

Figure CN119230778B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of battery material synthesis, and in particular relates to a method for in-situ gas-phase coating of a sodium ion battery positive electrode material with a metal-organic framework compound. Background Art
[0002] Sodium-ion batteries are abundant in resources and low in cost. As a potential supplement to lithium-ion batteries, they have gained significant attention in the fields of low-speed electric vehicles and energy storage. However, due to the large mass and high redox potential of sodium, the specific capacity and operating voltage of sodium-ion batteries are lower than those of lithium-ion batteries. Among the various cathodes of sodium-ion batteries, transition metal layered oxides exhibit the highest theoretical specific capacity. However, their low operating voltage range (2-4.0V) limits the improvement of the energy density of the cathode materials. In addition, layered oxide cathode materials have poor air stability and are affected by many environmental factors. Therefore, the development of cathode materials with high-voltage stability and air stability is crucial to improving the energy density and practical application of sodium-ion batteries.
[0003] Although the theoretical specific capacity of O3-nickel-manganese-based positive electrode materials is high, their operating voltage is often limited to less than 4.0V. The instability at high voltage levels (4.0-4.3V) usually comes from two aspects. On the one hand, the lattice deformation and shrinkage caused by irreversible phase change; on the other hand, more serious side reactions occur at the positive electrode-electrolyte interface, which subsequently lead to surface transition metal reduction, surface lattice heterogeneous reconstruction, metal ion dissolution and concurrent oxygen loss. The lost oxygen further stimulates the oxidation of the electrolyte, forming a vicious cycle. By coating and modifying the surface of the positive electrode material, not only can the direct contact between the electrolyte and the positive electrode material be isolated, effectively inhibiting the side reactions at the interface, but also the corrosion of water and carbon dioxide to the positive electrode material can be effectively isolated, and the air stability of the positive electrode material can be improved. However, the traditional solid-solid coating has problems such as uneven coating layer, poor consistency and high energy consumption, while the solid-liquid coating method is more complicated, with many experimental variables and poor repeatability. Summary of the invention
[0004] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a method for in-situ gas phase coating of sodium ion battery positive electrode materials with organic matter, which solves the problems of uneven coating layer thickness and poor repeatability in traditional solid-solid coating and solid-liquid coating methods. After coating, the high-voltage stability and air stability of the positive electrode material are significantly improved.
[0005] The technical solution of the present invention is as follows:
[0006] The present invention provides a method for in-situ gas-phase coating of sodium ion battery positive electrode materials with organic matter. Based on O3 type sodium ion battery layered oxide electrode materials, an amorphous coating layer is constructed on the oxide surface by low-pressure gas phase deposition method, and the thickness of the amorphous coating layer is 3-5nm.
[0007] Furthermore, the O3 type sodium ion battery layered oxide contains zinc.
[0008] Furthermore, the low-pressure vapor deposition method is to react the zinc-containing O3-type sodium ion battery layered oxide with the organic ligand at 80-150°C for 4-12h under -0.01 to -0.1MPa. Too high a temperature will intensify the thermal motion of the gaseous molecules, and the gaseous organic ligand will react more violently with the positive electrode material, and the coating layer will become thicker, thereby limiting the battery capacity; while the reaction temperature is too low, the vaporization temperature of the organic ligand cannot be reached, and the reaction cannot occur to form a uniform coating layer.
[0009] Further preferably, the low-pressure vapor deposition temperature is 100-140° C., the pressure is (-0.08) to (-0.1) MPa, and the reaction time is 8-10 h.
[0010] Furthermore, the organic ligand is an imidazole organic compound.
[0011] More preferably, the imidazole organic compound is one or more of 2-methylimidazole, 1,2-dimethylimidazole, and N-methylimidazole.
[0012] Furthermore, the preparation method of the zinc-containing O3 type sodium ion battery layered oxide is: sodium source and zinc source are weighed and mixed in proportion by wet ball milling to obtain a uniformly mixed precursor, and then the obtained precursor powder is calcined at high temperature to obtain a zinc-containing O3 type layered oxide positive electrode material.
[0013] Furthermore, the sodium source is one or both of sodium carbonate, sodium hydroxide or sodium acetate; the zinc source is one or both of zinc oxide or zinc acetate.
[0014] Furthermore, one or more of a nickel source, a manganese source, an iron source, and a titanium source are also ball-milled together with the sodium source and the zinc source.
[0015] Furthermore, the nickel source is one or more of nickel oxide and nickel trioxide.
[0016] Furthermore, the manganese source is one or more of manganese monoxide, manganese dioxide and manganese trioxide.
[0017] Furthermore, the iron source is one or more of ferrous oxide, ferrous oxide and ferrosoferric oxide.
[0018] Furthermore, the titanium source is one or more of titanium monoxide, titanium dioxide, and titanium trioxide.
[0019] Furthermore, the high temperature calcination temperature is 800-1000° C., the calcination atmosphere is air, nitrogen or oxygen, and the calcination time is 10-20 hours.
[0020] The present invention uses a low-pressure gas phase coating method to change the microstructure of the positive electrode material. Through transmission electron microscopy and spherical aberration correction electron microscopy, it is observed that in addition to the original layered structure on the surface of the positive electrode material, a new composite special phase structure of spinel phase and salt rock phase is formed. This special structure can stabilize the lattice oxygen on the outermost side of the particle, inhibit the release of oxygen on the surface of the material under high voltage, thereby improving its high-voltage stability; in addition, a uniform organic molecular layer is produced on the surface of the particle. This organic molecular layer forms a stable interface structure and a small gap structure through the coordination of metal and organic small molecules, which prevents water molecules and carbon dioxide in the air from directly contacting the active metal elements on the surface of the positive electrode material, avoiding Na + / H + Ion exchange process, thereby improving air stability.
[0021] Advantages and beneficial effects of the present invention:
[0022] (1) The thickness of the amorphous coating layer formed by the present invention is uniform and highly controllable, which is not achievable by conventional coating methods. After coating, the high-voltage stability and air stability of the positive electrode material are significantly improved. -1 The current density is 130mAh·g in the voltage range of 2-4.2V. -1 The specific capacity of the battery is 2000, and the capacity retention rate is more than 86% after 200 cycles. The sodium ion battery provided by the present invention has high specific capacity and excellent cycle stability.
[0023] (2) The organic ligand used in the present invention is low-cost, and the coating method involved is a solid-gas reaction process. The preparation process is simple, the reaction time is short, the temperature is low, the conditions are mild, and the energy consumption is reduced. It can be applied to commercial sodium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The sodium ion battery O3 phase layered oxide Na obtained in Example 1 0.9 Ni 0.32 Zn 0.08 Fe 0.1 Mn 0.4 Ti 0.2 XRD pattern of O2;
[0025] Figure 2 The O3-phase layered oxide Na obtained in Example 2 0.9 Ni 0.32 Zn 0.08 Fe 0.1 Mn 0.4 Ti 0.2 XRD pattern of the material after O2 coating;
[0026] Figure 3 This is the sodium ion battery charge and discharge curve of the coated material obtained in Example 1. (Active material loading: ~5 mg / cm 2 , current density: 200mA·g -1 , voltage window: 2-4.2V);
[0027] Figure 4 This is the sodium ion battery charge and discharge curve of the coated material obtained in Example 2. (Active material loading: ~5 mg / cm 2 , current density: 200mA·g -1 , voltage window: 2-4.2V);
[0028] Figure 5 This is the sodium ion battery charge and discharge curve of the coated material obtained in Example 3. (Active material loading: ~5 mg / cm 2 , current density: 200mA·g -1 , voltage window: 2-4.2V);
[0029] Figure 6 This is a capacity cycle comparison chart of Example 1 and Examples 1-3. (Active material loading: ~5 mg / cm 2 , current density: 200mA·g -1 , voltage window: 2-4.2V);
[0030] Figure 7 This is a TEM photo of the interface of the uncoated sodium ion battery positive electrode material of Comparative Example 1;
[0031] Figure 8 This is a TEM photo of the interface of the sodium ion battery positive electrode material of the reacted material obtained in Example 2;
[0032] Fig. 9 This is a TEM photo of the interface of the sodium ion battery positive electrode material obtained after the reaction in Comparative Example 2;
[0033] Fig.10 This is a TEM photo of the interface of the sodium ion battery positive electrode material of the reacted material obtained in Example 3. DETAILED DESCRIPTION
[0034] The present invention is described in detail and completely below with reference to the accompanying drawings.
[0035] The purity of the sodium carbonate, nickel oxide, zinc oxide, manganese dioxide, imidazole, 2-methylimidazole, 1,2-dimethylimidazole, N-methylimidazole and benzimidazole used in the examples is not less than 99%.
[0036] Comparative Example 1:
[0037] The carbonate and the oxide were mixed in a ball mill at a molar ratio of 0.9:1 and placed in a ball mill, and wet milled in a vertical ball mill at a speed of 600 r / min for 5 hours to obtain a uniformly mixed oxide precursor. The precursor material was dried, the powder was ground for 5 minutes, and then transferred to a corundum crucible, and kept at 900°C in a muffle furnace for 15 hours to obtain the initial O3 phase layered oxide material Na 0.9 Ni 0.32 Zn 0.08 Fe 0.1 Mn 0.4 Ti 0.2 O2, XRD see Figure 1 From the figure, it can be seen that the initial material is an O3 phase layered oxide structure without any impurities. TEM photos are shown in Figure 7 ,From the figure, we can see that the initial material has a smooth surface and complete particles.
[0038] Embodiment 1:
[0039] The initial O3 phase layered oxide material obtained in Comparative Example 1 and 2-methylimidazole were placed in a vacuum oven at a mass ratio of 1:1, and reacted for 8 hours at -0.1 MPa and 100°C in the vacuum oven to obtain a coated oxide positive electrode material.
[0040] Embodiment 2:
[0041] The initial O3-phase layered oxide material obtained in Comparative Example 1 and 2-methylimidazole were placed in a vacuum oven at a mass ratio of 1:1, and reacted for 8 hours at -0.1 MPa and 120°C to obtain a coated oxide positive electrode material. Figure 2 From the figure, it can be seen that the coating does not change the original phase structure of the material, and the material still maintains the O3 phase. Figure 8 From the figure, it can be seen that the darker part on the left is the layered oxide positive electrode material, and the outside of it is a uniform coating layer with a thickness of about 5 nanometers.
[0042] Embodiment 3:
[0043] The difference from Example 1 is that the reaction temperature is 140° C., the reaction is carried out for 8 hours, and a coated oxide positive electrode material is obtained.
[0044] Comparative Example 2:
[0045] The difference from Example 1 is that 2-methylimidazole is replaced by imidazole to obtain the oxide positive electrode material after the reaction. Fig. 9 ,It can be seen from the figure that replacing the ligand with imidazole cannot form a coating layer on the oxide surface.
[0046] Comparative Example 3:
[0047] The difference from Example 1 is that imidazole is replaced by benzimidazole to obtain the oxide positive electrode material after the reaction. Fig.10 ,It can be seen from the figure that replacing the ligand with benzimidazole cannot form a coating layer on the oxide surface.
[0048] Test Method
[0049] Preparation of sodium ion battery electrodes: High voltage stable sodium oxide positive electrode material, conductive agent Super P and binder PVDF are mixed evenly in a mass ratio of 8:1:1, and an appropriate amount of NMP is added to make a slurry. The slurry is evenly coated on aluminum foil and placed in a vacuum oven at 80°C for drying to make sodium ion battery electrode sheets.
[0050] Preparation of sodium ion battery: The sodium ion battery electrode sheet, diaphragm, electrolyte and negative electrode sheet are assembled in sequence in an argon atmosphere to finally obtain a sodium ion battery; the diaphragm is glass fiber; the solute in the electrolyte is 1M NaPF6, the solvent is EMC and PC, and the volume ratio of EMC and PC is 1:1. FEC is an additive, accounting for 2% of the volume of the electrolyte; the negative electrode sheet is a metal sodium sheet.
[0051] Test conditions
[0052] The high voltage stable sodium oxide positive electrode materials prepared in the examples and comparative examples were prepared into sodium ion battery pole pieces and sodium ion batteries. The prepared sodium ion batteries were tested at a temperature of 25°C, a voltage range of 2-4.2V, and a current of 200mA·g -1 The first cycle charge and discharge curve was obtained by testing at current density. -1 The capacity retention rate after 200 cycles was obtained by testing at a current density.
[0053] Figure 3 The sodium ion battery charge and discharge curve of the coated material obtained in Example 1 is shown in the figure. It can be seen from the figure that at 200 mA·g -1 Tested at current density, the battery's first cycle discharge capacity is 130.2mAh g -1 , the Coulomb efficiency in the first week was 89.8%.
[0054] Figure 4The sodium ion battery charge and discharge curve of the coated material obtained in Example 2 is shown in the figure. It can be seen from the figure that at 200 mA·g -1 Tested at current density, the battery's first cycle discharge capacity is 129.8 mAh g -1 , the Coulomb efficiency in the first week was 89.5%.
[0055] Figure 5 The sodium ion battery charge and discharge curve of the coated material obtained in Example 3 is shown in the figure. It can be seen from the figure that at 200mA·g -1 Tested at current density, the battery's first cycle discharge capacity is 130.7 mAh g -1 , the Coulomb efficiency in the first week was 89.7%.
[0056] Figure 6 It is a capacity cycle comparison diagram of comparative example 1 and embodiments 1-3. It can be seen from the figure that the cycle stability of embodiments 1-3 is better than that of comparative example 1, and the best capacity retention rate is embodiment 2, with a capacity retention rate of 87% after 200 cycles.
[0057] The above description is only a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several modifications and improvements without departing from the inventive concept, which all belong to the protection scope of the present invention.
Claims
1. A method for in-situ gas phase coating of sodium ion battery positive electrode materials with organic matter, characterized in that: Based on the zinc-containing O3-type sodium-ion battery layered oxide electrode material, an amorphous coating layer is constructed on the oxide surface by low-pressure vapor deposition. In addition to the original layered structure on the surface of the positive electrode material, a new composite special phase structure of spinel phase and salt rock phase is formed; The low-pressure vapor deposition method is to react the zinc-containing O3 type sodium ion battery layered oxide with an organic ligand at 80-150° C. for 4-12 hours at -0.01 to -0.1 MPa, wherein the zinc-containing O3 type sodium ion battery layered oxide also contains metallic sodium, nickel, iron, manganese, and titanium; The organic ligand is one or more of 2-methylimidazole, 1,2-dimethylimidazole and N-methylimidazole.
2. The method for in-situ gas phase coating of sodium ion battery positive electrode materials with organic matter according to claim 1, characterized in that: The reaction temperature is 100-140°C.
3. The method for in-situ gas phase coating of sodium ion battery positive electrode materials with organic matter according to claim 1, characterized in that: The preparation method of the zinc-containing O3 type sodium ion battery layered oxide is: sodium source, zinc source, nickel source, manganese source, iron source and titanium source are weighed and mixed in proportion by wet ball milling to obtain a uniformly mixed precursor, and then the obtained precursor powder is calcined at high temperature to obtain a zinc-containing O3 type layered oxide positive electrode material.
4. The method for in-situ gas phase coating of sodium ion battery positive electrode materials with organic matter according to claim 3, characterized in that: The sodium source is one or two of sodium carbonate, sodium hydroxide or sodium acetate; the zinc source is one or two of zinc oxide or zinc acetate.
5. The method for in-situ gas phase coating of sodium ion battery positive electrode materials with organic matter according to claim 3, characterized in that: The high temperature calcination temperature is 800-1000° C., the calcination atmosphere is air, nitrogen or oxygen, and the calcination time is 10-20 hours.
Citation Information
Patent Citations
Lithium ion battery negative electrode material and preparation method thereof
CN111082050A
High-performance sodium ion battery layered oxide electrode material
CN115377409A
O3-type nickel-iron-manganese-based sodium battery positive electrode material and preparation method thereof
CN117936748A